A study on the level of organisational citizenship behaviour in headquarters of Jabatan Kemajuan Masyarakat (KEMAS) Kuching / Dayang Annur Hidayah Abang Ismawi ... [et. al] - Abang Ismawi, Dayang Annur Hidayah; Kiprawi, Nur Aishah Hanim; Watson Awan, Willie (University Technology MARA Sarawak, 2011)
This research had been conducted by three student of Diploma of Public Administration from the Faculty of Administrative Science and Policies Studies under the supervision of Miss Noni Harianti binti Junaidi, and the lecturer of PAD340: Practical Training/Project Paper Sir Leftenant Colonel Saiful Anwar bin Md Ali. We are given the authority to complete this research with full of commitment and qualities. This research proposal is mainly about the level of Organisational Citizenship Behaviour in Community Development Department or also known as Jabatan Kemajuan Masyarakat (KEMAS) Kuching. This research generally to cover the aspect of the awareness of the KEMAS department regarding on the level of OCB and the working culture that relate with the level of OCB. Before we go to the study of the respondent survey, we must make a research from various books, articles, and any material resources of information to be used as our main sources to identify which factors are relevant as a guideline for our survey. There will be having various types of research methodologies that are being used in order to have a systematic process of researching.